Problem analysis of the implementation of the AIR and ALC methods in Islamic Religious Education learning at SMAN 9 Malang - Azzahroh, Delfina Aurora; Ferdiansyah, Mochamad Ariel (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Student-centered learning remains difficult to implement in Islamic Religious Education (PAI), where teacher-centered habits, limited engagement, and weak pedagogical adaptation persist. Although the AIR and ALC methods are promoted as active-learning approaches, little is known about how they function when applied simultaneously in actual PAI classrooms. This study addresses that gap by examining the integration process of AIR and ALC and the contextual factors shaping their effectiveness at a senior high school in Malang. Using a qualitative case-study design, data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. Findings show that AIR strengthens cognitive processing through auditory engagement and repetition, while ALC structures the learning flow to sustain participation. However, their implementation is hindered by classroom discipline issues, low student motivation, limited teacher readiness, scheduling constraints, and infrastructural shortcomings. These results indicate that contextual conditions, rather than the methods themselves, determine the success of AIR–ALC integration in PAI learning.